2012
DOI: 10.1063/1.4768909
|View full text |Cite
|
Sign up to set email alerts
|

Role of wrinkle height in friction variation with number of graphene layers

Abstract: Molecular dynamics simulations are performed to study the frictional behavior of graphene. It is found that the friction between a diamond tip and graphene decreases with increasing number of graphene layers. This behavior is also affected by the graphene sheet size; specifically, the effect of the number of layers on friction becomes significant only when the modeled graphene sheets exceed a critical length. We further show that the frictional behavior can be directly correlated to the height of near-contact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 12 publications
8
79
0
Order By: Relevance
“…These measurements revealed that graphene maintains its corrugation level even after it is refolded onto an atomically flat substrate and that both the graphene and the substrate must be ultraflat to achieve the intimate contact necessary for strong adhesion and low friction. The interpretation of the observation of Lee et al was supported by the Brownian dynamics simulations of Smolyanitsky et al [59] and by the molecular dynamics simulations of Ye et al [60]. The tip-induced out-of-plane deformation of 2D materials was also experimentally confirmed and systematically studied by Barboza et al [61].…”
Section: Dependence Of Friction On Layer Number and Substratesupporting
confidence: 58%
“…These measurements revealed that graphene maintains its corrugation level even after it is refolded onto an atomically flat substrate and that both the graphene and the substrate must be ultraflat to achieve the intimate contact necessary for strong adhesion and low friction. The interpretation of the observation of Lee et al was supported by the Brownian dynamics simulations of Smolyanitsky et al [59] and by the molecular dynamics simulations of Ye et al [60]. The tip-induced out-of-plane deformation of 2D materials was also experimentally confirmed and systematically studied by Barboza et al [61].…”
Section: Dependence Of Friction On Layer Number and Substratesupporting
confidence: 58%
“…Their results support the hypothesis and explain the decreasing friction by the ability of multilayers to act as single material and resist wrinkling [36]. Dong et al have analyzed the results of atomistic simulations of friction on hydrogenated graphene [37].…”
Section: Atomistic Simulations Of Graphene Tribologymentioning
confidence: 64%
“…Friction increases because graphene deformations enhance the real contact area at the tip apex. In this interpretation, the amount of deformation decreases with increasing number of layers, as revealed by computer simulations [109][110][111][112], with the result that friction diminishes for increasing graphene thickness.…”
Section: Layered Materialsmentioning
confidence: 93%
“…This system exhibits a completely commensurate or incommensurate interface as a function of the misfit angle and a systematic computational study of the interlayer interaction energy in a rigid bi-layer graphene sys- Figure 3. Atomistic simulation of a graphene nanoribbon (GNR) deposited over a gold (111) surface and driven by an AFM tip, resembling the experimental setup of Ref. [70].…”
Section: Contact Area Dependence and New Perspectives In Superlubricitymentioning
confidence: 99%